The regional dimension of taxes and public expenditure in Ireland - Edgar Morgenroth (The Economic and Social Research Institute (ESRI), 2007)
In Ireland as in many other countries there has been an ongoing debate on the nature, degree and trends of regional imbalance, which has led to substantial research output. While much is now known about these trends, the degree to which they are ameliorated by existing public policies has not been systematically examined. This paper considers two aspects of public policy namely the fiscal system and public expenditure. In particular regional government accounts are constructed, which identify the level of taxation, subsidisation and public expenditure at the regional level. These are then used to identify the degree of regional re-distribution. That analysis confirms that the fiscal system does reduce relative income differences in Ireland. Dublin and the South-West contribute to a substantial resource transfer to other regions. In contrast to the findings for the UK, the level of transfers is found to be highly related to the state of development. In other words the fiscal system works in a progressive manner in relation to regional disparities. Nevertheless the better off regions receive an above average level of expenditure so that the system only partially equalises.
Keywords: H72; H77; R11; 330; Regional Disparities; Government Expenditure; Taxes; Öffentliche Ausgaben; Steuer; Regionale Disparität; Irland